A study on on-line education (e-learning) in advanced cardiac life support among health care professionals in Hospital Universiti Sains Malaysia - Baladas, Jeewadas A/L Velummylum Baladas (2018)
INTRODUCTION : ACLS is extensively practiced to equip health care professionals to deal with cardiac related emergencies. E-learning provides a platform for easier accessibility of learning materials and a more personalized learning schedule at a lower overall cost. The aim of this study is to compare the outcome of e-learning ACLS (e- ACLS) courses versus conventional ACLS (c-ACLS) courses and measure its effectiveness among health care professionals in HUSM. This study also aims to determine the attitude on e-learning among health care professionals in HUSM. METHODS : A total of 96 candidates attended ACLS courses in Hospital Universiti Sains Malaysia (HUSM) between 1st January 2016 and 30th May 2017. Fourty-eight candidates were enrolled on a c-ACLS course and 48 on an e-ACLS course. Candidates participating in c-ACLS course undertook the 2-day face-to-face course. Candidates participating in e-ACLS course completed 6-8 hours of online e-learning lecture videos prior to attending the one day modified face-to-face course. All candidates were assessed by pre- and post-course MCQ and practical cardiac arrest simulation (CAS-test). Only post course & CAS-test marks contributes to the pass or fail of the candidates. Demographic data were collected in addition to assessment outcomes. RESULTS : Candidates on the e-ACLS course had higher mean scores on the pre-course MCQ (69.1, SD 19.1) compared to those on the c-ACLS course (58.6, SD 16.6, P<0.001). Similarly, they had higher mean scores on the post-course MCQ (e-ACLS 78.9, SD 12.0 vs. c-ACLS 70.6, SD 13.9; P<0.001). The CAS-test pass rate on the e-ACLS course was higher thanthe pass rate on the c-ACLS course (95.8% vs. 87.5%; P=0.13). The overall pass rate was 93.8% for candidates in the e-ACLS versus 83.3% in c-ACLS courses (P=0.09). Majority of candidates have a positive attitude towards e-learning and agreed that it could be used as an adjunct to face-to-face instructor teaching. CONCLUSION : The e-ACLS course demonstrates better results when compared to traditional conventional face-to-face learning (c-ACLS) in equipping candidates with ACLS skills. Added benefit occurs when considering increased candidate autonomy, cost-effectiveness, decreased instructor burden and improved standardization of course material. Further dissemination of the e-ACLS course should be encouraged in view of the benefits.